Targeting Creativity Through a Learner-Generated Digital Storytelling Project - Tisoglu, Secil; Piri, Zeynep; Mericelli, Murat; Catan Inan, Funda (The Institute of Education of Tsinghua University, 2022)
One of the most emphasized skills for social, educational and workplace settings is creativity in the present decade. This study aims to understand whether a collaborative digital storytelling production project improves the creativity of undergraduate students. 109 students engaged in group work and employed a range of digital tools (i.e. wikis, storyboard creation tools, video editing programs) for creating digital stories about the 21stcentury problems they think relevant. Students were able to review and comment on each other’s scenarios and pres ent their digital stories to their classmates at the end of the project. The adapted version of ‘How Creative Are You?’ scale (Whetten & Cameron, 2011) was used for measuring the students’ creativity scores before and after the implementation. Whereas resu lts indicated that creativity scores were increased by the digital storytelling production project, this effect was not significant. However, observation of the production process revealed some components of creative thinking skills of students.
Keywords: 4. Education